Family Disintegration in Libyan Society (Causes, Effects, and Treatments): A Theoretical Analytical Study - Dr. Mouaied Gumah Abohmeda (Journal of Libyan Academy Bani Walid, 2025)
This research aims to study family disintegration in Libyan society, as it is one of the contemporary social issues that threaten family cohesion and societal stability. The research problem was to answer the main question: What are the causes and effects of family disintegration, and what are the means to address it and limit its spread? The research adopted a descriptive and analytical approach. Its main objectives were to identify the causes and factors leading to family disintegration and analyze its effects on the individual, family, and society. The research reached a set of conclusions, the most prominent of which was that family disintegration is the result of a complex interaction between several economic, social, psychological, and cultural factors, resulting in extremely serious consequences that affect family stability. In light of this, the research reached a set of therapeutic solutions, represented by strengthening family counseling, supporting families economically and socially, and activating the role of relevant institutions.